Perbandingan Hukum Perlindungan Konsumen Terkait Jasa Titip Tiket di Indonesia dan Amerika Serikat - Ester Gloria Anastasia; Ratna Artha Windari; Ni Ketut Sari Adnyani (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2026)
This study analyzes consumer legal protection in the practice of digital concert ticket concierge services in Indonesia based on the right to "accurate, clear, and honest" information under Article 4(c) of the Consumer Protection Law (UUPK), and compares it with the standards in Section 5 of the Federal Trade Commission Act in the United States. Using a normative method with statutory and comparative approaches, the research finds that concierge service practices operate in a specific regulatory vacuum. The norm in the UUPK is vague and inoperable, while protection through civil law and the Electronic Information and Transactions Law (ITE Law) is proven to be limited. In contrast, the system in the United States, administered by the Federal Trade Commission (FTC), is more effective with objective evaluation standards, the reasonable consumer standard principle, and proactive enforcement mechanisms. It is concluded that Indonesia requires regulatory reform that adopts a more operational approach from the US.